Risk Disclosures and Key Performance Indicators In Non-Financial Reporting - Theoretical Issues - Monika Turek-Radwan; Anna Mazurczak-Mąka; Katarzyna Świetla (Communications of International Proceedings, 2025)
The aim of this article is to analyse the role, scope and applicable legal provisions concerning non-financial risks in business entities. Disclosure of non-financial risks is currently an important tool used in management and promotes sustainable development for potential shareholders. Providing truthful, material and relevant information is perceived to be critical issue for the proper functioning of capital markets as it enables  appropriate evaluation of companies’ risk profiles and future prospects. One of the important elements of non-financial reporting are key performance indicators, which can be successfully used to inform stakeholders about company’s achievements in activities regarding social and environmental issues. Their numerical dimension makes them measurable and in comparison to narrative disclosures, non-financial KPIs can be easier to compare over time.
Keywords: risk; non-financial reporting; CSRD; ESG; key performance indicator.